Gambaran Penggunaan Obat Bahan Alam dan Potensi Interaksinya pada Pasien Hipertensi dan Diabetes Melitus Peserta PROLANIS di Kota Yogyakarta - Artha Woro Utami; Trilestari Trilestari; Ismiyati Ismiyati; Gita Mayasari; Muhammad Senoaji Wibowo; Restu Istya Ambari Putra; Rygyna Selkly Prihatin; Senlia Nur Eka Saputri; Sherly Amelia; Triyani Triyani (Universitas Hamzanwadi, 2026)
Hypertension and diabetes mellitus are the non-communicable diseases with the highest prevalence in the Special Region of Yogyakarta. The use of herbal medicines (obat bahan alam, OBA) as complementary therapy has grown among chronic disease patients, including in Program Pengelolaan Penyakit Kronis (PROLANIS) participants, yet OBA profiles and their potential drug interactions remain poorly characterized in this population. This study described OBA use profiles among hypertensive and diabetic PROLANIS participants at primary health centers in Yogyakarta City. A descriptive cross-sectional study was conducted at five primary health centers (Puskesmas) in Yogyakarta City from January to May 2025. A total of 160 respondents (hypertension n=115, diabetes mellitus n=45) were enrolled through consecutive sampling, and data were collected via structured face-to-face interviews and analyzed descriptively. Respondents were predominantly female (70.0%), aged 65 years or older (48.8%), and housewives (52.5%). In the hypertension group, the most commonly used OBAs were kunyit asam (28.7%), beras kencur (20.9%), and ginger (20.0%); in the diabetes mellitus group, kunyit asam (26.7%), turmeric (22.2%), and jahe (20.0%) predominated. Most OBAs were taken as liquid preparations (80.0%), sourced from tukang jamu (45.0%) or prepared at home (44.4%). Friends and relatives were the primary information source (68.1%), while only 3.1% of respondents received information from healthcare providers. Cross-tabulation of the 47 respondents currently using OBA revealed amlodipine combined with kunyit (turmeric) as the most frequent drug-herb combination, with pharmacokinetic interaction potential via CYP3A4 inhibition. Perceived therapeutic benefit was reported by 75.6% of respondents, and 77.5% intended to continue using OBA. OBA use is widespread among PROLANIS participants, and combinations carrying pharmacokinetic interaction risk, notably kunyit with amlodipine or angiotensin receptor blockers, and hypoglycemic OBAs with sulfonylureas and insulin, warrant systematic monitoring. Pharmacist-led OBA counselling at primary health facilities should be strengthened.